Investigation of creep damage in advanced martensitic chromium steel weldments using synchrotron X-ray micro-tomography and EBSD. (March 2015) - Schlacher, C.; Pelzmann, T.; Béal, C.; Sommitsch, C.; Gupta, C.; Toda, H.; Mayr, P.
<x content-type="archive" xml:space="preserve">Abstract</x> In recent years, a design concept for the stabilisation of the microstructure by addition of boron and nitrogen was developed. This so called martensitic boron–nitrogen strengthened steel (MARBN) combines boron strengthening by solid solution with precipitation strengthening by finely dispersed nitrides. Welded joints of MARBN steels showed no formation of a uniform fine grained region in the heat affected zone (HAZ) which is in general highly susceptible to Type IV cracking. In this work, the crossweld creep strength of a newly developed MARBN steel was analysed and the evolution of damage was investigated using synchrotron microtomography supported by electron microscopy. Three-dimensional (3D) reconstructions of the tested samples together with electron backscatter diffraction investigations revealed an intense void formation in a restricted area along small grains at prior austenite grain boundaries in the HAZ as the main reason for premature creep failures in the HAZ of welded joints.